Kejahatan Bahasa di Wilayah Hukum Papua Barat: Kajian Linguistik Forensik - Hugo Warami (Ranah: Jurnal Kajian Bahasa, 2022)
The problem of language crime has recently become a serious problem that is being faced by linguists and law enforcement officials. This language crime problem includes: interdisciplinary aspects between the worlds of language, law, and crime. The current facts prove that in analyzing the Investigation Report (BAP) regarding the investigation of a legal case in the legal territory of West Papua, it was found that the results of the investigation and investigation required a linguist. For this reason, this study aims to describe the branch of forensic linguistics that is present to bridge language facts and legal facts as one of the supporting aspects in providing proof of a case in court. This study uses two approaches, namely (1) a theoretical approach and (2) a methodological approach. The theoretical approach is an exploration of Forensic Linguistic theory, while the methodological approach is a descriptive approach with an explanatory dimension. This study uses forensic linguistic theory as the main umbrella in exploring language facts that contain elements/meanings of language crimes. This study is explored from the perspective of forensic linguistics by referring to the phenomenon of the results of investigations and case investigations in the jurisdiction of West Papua. The objects in this study consist of three cases, namely (1) Defamation, (2) Humiliation, and (3) Fraud. The results of the analysis illustrate that forensic linguistics becomes a strong tool of evidence in decisions that have legal implications by considering linguistic features and their suitability with legal facts in disentangling types of crimes in the text and context as well as interactions between two or more parties in language crimes. AbstrakMasalah kejahatan bahasa akhir-akhir ini menjadi masalah serius yang sedang dihadapi oleh ahli bahasa dan aparat penegak hukum. Masalah kejahatan bahasa ini mencakup: aspek interdisipliner antara dunia bahasa, hukum, dan kejahatan. Fakta saat ini membuktikan bahwa dalam menganalisis Berita Acara Pemeriksaan (BAP) tentang investigasi atas sebuah kasus hukum di wilayah hukum Papua Barat, dijumpai bahwa hasil penyidikan maupun penyelidikan memerlukan ahli bahasa. Untuk itu, kajian ini bertujuan mendeskripsikan cabang linguistik forensik yang hadir menjembatani fakta bahasa dan fakta hukum sebagai salah satu aspek pendukung dalam memberikan pembuktian sebuah perkara di pengadilan. Kajian ini menggunakan dua pendekatan, yakni (1) pendekatan teoretis dan (2) pendekatan metodologis. Pendekatan teoretis adalah eksplorasi teori Linguistik Forensik, sedangkan pendekatan metodologi adalah pendekatan deskriptif dengan dimensi eksplanatif. Kajian ini menggunakan teori linguistik forensik sebagai payung utama dalam mengeksplorasi fakta-fakta bahasa yang mengandung unsur/makna kejahatan bahasa. Kajian ini dieksplorasi melalui perspektif linguistik forensik dengan mengacu pada fenomena hasil penyidikan dan penyelidikan kasus di wilayah hukum Papua Barat. Objek dalam kajian ini terdiri atas tiga kasus, yakni (1) Pencemaran Nama Baik, (2) Penghinaan, dan (3) Penipuan. Hasil analisis menggambarkan bahwa linguistik forensik menjadi alat bukti kuat dalam keputusan-keputusan yang berdampak hukum dengan pertimbangan fitur linguistik dan kesesuaiannya dengan fakta hukum dalam mengurai jenis kejahatan pada teks dan konteks serta interaksi antara dua pihak atau lebih dalam tindak kejahatan bahasa.